1984
DOI: 10.1080/00365521.1984.12005827
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Dysplasia in Ulcerative Colitis

Abstract: Epithelial dysplasia was found in the large intestine of 8 of 15 patients with ulcerative colitis operated on between 1980 and 1982. In six of eight patients, dysplasia was found in the cecum and ascending colon, in one of eight in the descending or sigmoid colon, and in four of eight in the rectum. None of the five carcinomas in three patients were located in the sigmoid colon or rectum. The age of onset was much lower, 19 +/- 7 years, and the duration of colitis longer, 15 +/- 7 years, for the group with dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In our experiment, DMH and DSS induced colitis-related tumors dominant in the distal part of colon followed by in the middle part. In human UC, dysplasia was found in two or more segments in 42-75% of the cases and the incidence of mutiple synchronous cancers was reported to vary from 22-50% [20][21][22] . In the current study, the result also showed that dysplasia was present in two or more segment in 60% of the animals and the incidence of synchronous cancers was 33.3%.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, DMH and DSS induced colitis-related tumors dominant in the distal part of colon followed by in the middle part. In human UC, dysplasia was found in two or more segments in 42-75% of the cases and the incidence of mutiple synchronous cancers was reported to vary from 22-50% [20][21][22] . In the current study, the result also showed that dysplasia was present in two or more segment in 60% of the animals and the incidence of synchronous cancers was 33.3%.…”
Section: Discussionmentioning
confidence: 99%
“…An underestimation of the real prevalence of dysplasia due to a ‘loss of dysplasia data’ could be an option in our study despite the fact that colectomy rates and post-surgery specimen pathology was available [47]. Our patients have been followed up for 10 years from diagnosis, so our study has probably limited value for assessing dysplasia as a marker for cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence of carcinoma in patients with ulcerative colitis is approximately 5 % (McDougall 1964; Gozzetti et al 1987). Patients with ulcerative colitis, when compared with those without colitis, develop color ectal cancer at a younger age, often at multiple sites in the colon and frequently present at sites other than the rectum or sigmoid colon (Greenstein et al 1979;Vatn 1984). There appears to be a higher incidence of synchronous cancers in ulcerative colitis than in a control population, and also the cancers in ulcerative colitis tend to be less well differentiated.…”
Section: Kumarmentioning
confidence: 99%